Nivolumab as adjuvant treatment for a spinal melanocytoma: A case report. Issue 19 (14th May 2021) - Hean, Virginie; Bouleftour, Wafa; Ramirez, Carole; Forest, Fabien; Boutet, Claire; Rivoirard, Romain
Abstract: Rationale: Meningeal melanocytoma is a rare benign melanocytic tumor of the central nervous system. We report for the first time a case of meningeal melanocytoma treated with immunotherapy. Patient concerns: A 70-year-old man with no medical history was admitted to the Emergency Room. He suffered from a motor and sensory deficit in his left lower limb and a bilateral upper arm neuralgia. Diagnoses: A contrast-enhanced magnetic resonance imaging (MRI) was performed. It showed a C7-T1 bleeding intramedullary tumor. Laminectomy was decided and performed. The results of the pathologic examination showed a melanocytic tumor harboring GNAQ mutation. Meningeal melanocytoma was the final diagnosis. Interventions: The patient was treated with 10 radiotherapy sessions and 6 cycles of nivolumab. A year later, the patient experienced neuralgia again with severe pain and an increasing sensory motor deficit. He underwent a second surgery that was incomplete. As the tumor kept growing, he received temozolomide. But the 6th cycle had to be interrupted due to bedsore infection in the hip area. Outcomes: Disease progression finally led to the patient's death 3 years after diagnosis. Lessons: This case report is the first about a patient with meningeal melanocytoma treated with immunotherapy. Treatment based on biomolecular mutations will probably change spinal melanocytoma therapeutic approach in the next few years.